Main Drivers of Battery Industry Changes: Electric Vehicles—A Market Overview - Dmitry V. Pelegov; José Pontes (Batteries, 2018)
The growing popularity of electric vehicles is one of the main drivers of battery industry transformation. Words like “transport system decarbonization„, “electromobility„, and “environmental-friendly society„ are very popular today, but questions remain as to how to measure electric vehicles’ adoption progress and how this transition changes the battery industry. This perspective paper provides a review of the electric cars and buses market, estimates the production volumes of some other electric vehicle types, and discusses the role of traction batteries in the global battery market. A simple estimation of the sales rate allows us to evaluate the prospects of electric vehicle adoption in leading countries. Finally, the application of the main battery chemistries is reviewed and topical issues to the research society are addressed and formulated.